A rare hepatic artery variant reporting and a new classification - Wu, Xiaojing; Kang, Jianxiong; Liu, Yuwei; Sun, Guodong; Shi, Ying; Niu, Junqi (Frontiers in Surgery, 2022)
Variations of the hepatic artery are very common, but they greatly increase the difficulty of surgery and the risk of complications in perihepatic surgeries such as liver transplantation, liver segmentectomy, and gastroduodenal surgery. Thus, it is important to precisely define the type of hepatic artery variant before surgery. However, there are often rare variants that cannot be defined with existing classifications. For example, the type of hepatic artery variant in the current case could not be classified with conventional classifications, and no such variation has been reported to date, involving two accessory left hepatic arteries from the common hepatic and left inferior phrenic arteries, respectively. Based on the existing 3DCT technology and the CRL classification method, which is applicable to the most common hepatic artery variants, we reviewed many rare variant types and proposed a new classification method (ex-CRL classification) for hepatic artery variations that do not fit the classic scope. The ex-CRL classification can accurately classify the vast majority of rare cases in the literature, greatly compensates for the limitations of current hepatic artery classifications, improves the generalization and understanding of rare cases, and reduces surgical complications.